Tailoring the chiral magnetic interaction between two individual atoms - A. A. Khajetoorians (Nature Portfolio, 2016)
The Dzyaloshinskii-Moriya exchange interaction arises in magnetic systems with broken inversion symmetry and promotes chiral magnetic order which may be exploited in spintronic devices. Here, the authors demonstrate how such an interaction between magnetic atoms on a metallic surface may be tuned by their separation.